2010
DOI: 10.1080/14486563.2010.9725260
|View full text |Cite
|
Sign up to set email alerts
|

Beyond threat- and asset-based approaches to natural resource management in Australia

Abstract: This article examines the origins, strengths and weaknesses of these threat-based and asset-based approaches. A third approach is then proposed that c o m b i n e s t h e b e s t o f b o t h b y f o c u s i n g o n t h e maintenance and measurement of environmental condition at the most appropriate scales from local to national. It is suggested that such a hybrid 'conditionbased' approach would involve:1. setting realistic and achievable resource condition targets by acknowledging current and potential resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 21 publications
0
20
0
1
Order By: Relevance
“…. Others are worried that the claims of efficacy and cost-effectiveness have not been substantiated, and that we don't yet have functioning markets for environmental services (Curtis and Lefroy 2010).…”
Section: Nrm Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…. Others are worried that the claims of efficacy and cost-effectiveness have not been substantiated, and that we don't yet have functioning markets for environmental services (Curtis and Lefroy 2010).…”
Section: Nrm Evolutionmentioning
confidence: 99%
“…Some have suggested that our drive for efficiency may have come at the cost of effectiveness (Curtis and Lefroy 2010). Several audit reports on national NRM programs have pointed out that a lack of monitoring of outcomes and a focus on outputs rather than outcomes has made it impossible to determine whether this new approach is working (ANAO 2008(ANAO , 2014.…”
Section: Evolution or Devolution?mentioning
confidence: 99%
See 1 more Smart Citation
“…Institutional approaches to conserving biodiversity are diverse, but can be grouped into three broad categories: 1) protecting assets, 2) responding to threats, or 3) supporting the conditions of ecosystem processes (Curtis and Lefroy, 2010). Driven by legislative frameworks, many conservation initiatives tend to focus on the conservation of individual assets (e.g.…”
mentioning
confidence: 99%
“…This means that in practice many countries, such as Australia, tend to focus time and investment on the first two categories. While efficient, this can be a source of institutional misfit, as it tends to neglect the broader social--ecological context and underlying causes of biodiversity decline (Clement et al, 2016;Curtis and Lefroy, 2010).…”
mentioning
confidence: 99%